Consumer Online Purchase Decisions Through Return Guarantee And Cash On Delivery (COD) Services Among Generation Z Users of The Shopee Application In Sungai Jawi Pontianak: Keputusan Pembelian Konsumen Secara Online Melalui Jaminan Pengembalian Dan Layanan Cash On Delivery (Cod) Pada Generasi Z Sungai Jawi Pontianak Pengguna Aplikasi Shopee - Nurul Septya Magisa (Journal of Management Specialists, 2023)
This research aims to determine the influence of return guarantee and cash on delivery (COD) services on the purchasing decisions of Generation Z users of the Shopee application in Sungai Jawi, Pontianak. The research type used in this study is descriptive research with a quantitative approach. The sample in this study consisted of 90 respondents. The sampling technique used in the research is purposive sampling, where each element in the population does not have an equal chance of being selected as a sample. Data collection techniques used a questionnaire distributed to Generation Z in Sungai Jawi, Pontianak. The instrument testing technique in this study includes validity and reliability tests, while hypothesis testing uses multiple linear regression tests, partial tests (t), and Adjusted R2 tests. Based on the multiple linear regression results, partially, the return guarantee variable has a positive influence on purchase decisions with a significant value of 0.000 < 0.05 and a t-value of 5.430 > 1.662, and the cash on delivery service variable with a significant value of 0.000 < 0.05 and a t-value of 3.766 > t-table 1.662. Based on the testing of adjusted R2, both X variables (return guarantee and COD service) together have an influence on the Y variable of 36.8%, while the remaining 63.2% (e value) is influenced by other variables not included in this research model, such as variables outside the scope of this study